2014
DOI: 10.1016/j.renene.2013.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biofertilizer quality and health implications of anaerobic digestion effluent of cow dung and chicken droppings

Abstract: a b s t r a c tAnaerobic digestate have been identified as a rich source of essential plant nutrients. Nevertheless, its safety measured by the concentration of pathogen present is of great concern to end users. This research explored the efficiency of the mesophilic biodigestion process in the stabilization and sanitization of cow dung and chicken droppings. Six (6) kg each of cow dung and chicken droppings were collected fresh and free from impurities, pre-fermented, mixed with water in the ratio 1:1 w/v to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 10 publications
5
60
0
8
Order By: Relevance
“…For example, Alfa et al (2014) showed that while E. coli and Shigella sp. were effectively removed via AD, species of Salmonella and Klebsiella survived.…”
Section: Pathogen Regrowthmentioning
confidence: 99%
“…For example, Alfa et al (2014) showed that while E. coli and Shigella sp. were effectively removed via AD, species of Salmonella and Klebsiella survived.…”
Section: Pathogen Regrowthmentioning
confidence: 99%
“…The following model was used (Eq. 6): (6) where the SF max , % is the maximum solubilization factor, L is the time when SF , is equal to ½ of SF max and k, 1/day constant is the variable slope which is called the Hill slope. When k is greater the curve changes more sharply and it means that solubilization process is performed faster.…”
Section: Solubilization Factormentioning
confidence: 99%
“…Many accelerate certain microbial processes in the soil and mobilize nutrients from non-usable to usable form through biological processes [6]. Some bacteria produce acids or enzymes as metabolites and thus are able to solubilize phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014 M. I. Alfa et al [21] had proposed the efficiency of the mesophilic bio digestion process in the stabilization and sanitization of cow dung and chicken droppings. Six (6) kg each of cow dung and chicken droppings were collected fresh and free from impurities, pre-fermented, mixed with water in the ratio 1:1 w/v to form slurry, fed into the respective reactors and digested for 30 days at an average ambient temperature of 30degree centigrade.…”
Section: Literature Reviewmentioning
confidence: 99%